PREVALENCE OF OBESITY IN SCHOOL CHILDREN OF HAZARA DIVISION - Haq, Israr ul; Siddiqu, Tahir Saeed; Jan, Muhammad Ali (Journal of Ayub Medical College Abbottabad, 2010)
Background: Limited data is available in Pakistan regarding prevalence of obesity in school going children. The objective of this study was to find out obesity prevalence in school going children in Hazara division. Methods: It was descriptive study. Data of 3200 students was collected over six month period, from Hazara Division. Four schools were selected in each district two for boys and two for females. District Kohistan was excluded from study as female education is not permitted beyond primary education. Children 5-14 year age group were included in the study. Initial 20 students of each class were selected for study. Anthropometric data (weight, height) for each student was collected and entered on Performa structured for this purpose. BMI was calculated and values were compared with standard BMI charts of National Health Centre for health statistics. Results: Prevalence of obesity was 4.78%. Out of 3,200 children enrolled 153 (4.78%) were obese. Male to female ratio was 1:1.2. The prevalence of obesity was high in private school students than government schools (66.66% and 33%). The prevalence was high in both sexes in 12-14 years and 6-7 years age groups (49% and 20.26%). Conclusion: Prevalence of obesity in present study is similar to the results from developing countries in the region but prevalence is lower than developed countries. Problem of obesity also exists in developing countries and there is need to create awareness about obesity and related complications. Keywords: Obesity, BMI, Nutrition, Hazara, Children